Is military advertising effective? : an estimation methodology and applications to recruiting in the 1980s and 90s - Dertouzos, James N., 1950- (Rand, 2003)
The Defense Department has been spending over $100 million annually on recruiting advertising. Previous econometric studies of military advertising's effects have relied on data from time periods unlike today's and have used models possibly inappropriate for supporting today's decisionmakers. This report details improved methods developed to assess military advertising's effectiveness and illustrates them using early 1980s and mid-1990s data.